1993
DOI: 10.1161/01.cir.87.4.1378
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diastolic function during development and correction of chronic LV volume overload produced by mitral regurgitation.

Abstract: Background. Mitral regurgitation (MR) causes an augmentation in left ventricular (LV) diastolic function, increasing early diastolic filling rate and decreasing LV stiffness. Whether these changes in diastolic function persist, return to normal, or become abnormal after mitral valve replacement (MVR) is unknown.Methods and Results. Simultaneous LV echocardiography and catheterization studies were performed in six dogs in the baseline state (baseline), 3 months after creation of MR (chronic MR), and 3 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…Also, patients with chronic MR have preserved LV relaxation and decreased LV stiffness to compensate for the volume overload. 32 These previous findings may be consistent with the findings of the present study. LA remodeling and AF are surrogate markers of LV diastolic dysfunction.…”
Section: Parameters Of 3d-teesupporting
confidence: 94%
“…Also, patients with chronic MR have preserved LV relaxation and decreased LV stiffness to compensate for the volume overload. 32 These previous findings may be consistent with the findings of the present study. LA remodeling and AF are surrogate markers of LV diastolic dysfunction.…”
Section: Parameters Of 3d-teesupporting
confidence: 94%
“…In a similar chronic canine model (22,36), chamber dilatation is also seen without a reduction in EF. However, in this model, there is no progressive change in the severity of the MR.…”
Section: Discussionmentioning
confidence: 92%
“…Zile et al have demonstrated a shift to the right of the pressure-volume curve in dogs with mitral regurgitation. 33 They also found that chamber stiffness decreased in response to the volume load. Fragata and Areias 34 showed that smallto-moderate volume load induced by infusion of saline to dogs resulted in an increase in early filling and improved compliance, while severe acute volume load resulted in a shift in filling toward late diastole and decreased compliance.…”
Section: Effect Of Pregnancy On Diastolic Functionmentioning
confidence: 97%